2009
DOI: 10.1186/1471-2164-10-35
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gene expression profiles for different types of mast cells pooled from mouse stomach subregions by an RNA amplification method

Abstract: Background: Mast cells (MCs) play pivotal roles in allergy and innate immunity and consist of heterogenous subclasses. However, the molecular basis determining the different characteristics of these multiple MC subclasses remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…It was noteworthy that a drastic downregulation of Hdc, which encodes the enzyme responsible for histamine synthesis, was unexpectedly observed (Figure 1e). We previously demonstrated that Ptgr1, which encodes the enzyme involved in inactivation of the eicosanoids, was expressed in the mucosal mast cells, not in the connective-tissue-type mast cells in murine stomach [20]. Expression of Ptgr1 was found to be moderately upregulated in our system (Figure 1f).…”
Section: Combination Of Il-9 and Scf Induced Expression Of Mcpt1 And mentioning
confidence: 52%
“…It was noteworthy that a drastic downregulation of Hdc, which encodes the enzyme responsible for histamine synthesis, was unexpectedly observed (Figure 1e). We previously demonstrated that Ptgr1, which encodes the enzyme involved in inactivation of the eicosanoids, was expressed in the mucosal mast cells, not in the connective-tissue-type mast cells in murine stomach [20]. Expression of Ptgr1 was found to be moderately upregulated in our system (Figure 1f).…”
Section: Combination Of Il-9 and Scf Induced Expression Of Mcpt1 And mentioning
confidence: 52%
“…Cellular and extracellular matrix tissue microenvironment where mast cells are located alters mast cell responsiveness through effects on the cells by adhesive interactions . These interactions point out to biological significance of priming through cytoskeletal reorganization.…”
Section: Cytoskeleton and Mast Cell Primingmentioning
confidence: 99%
“…Serine hydrolases may be responsible for the cinnamoyl esterase activity of the gastrointestinal mucosa; these carboxylesterases share similar structural homology and mechanism of hydrolysis with cinnamoyl esterases such as FAEA from Aspergillus niger. Serine hydrolases have been located in mast cells of the small intestine mucosa (Huntley et al, 1985), and more recently, mast cells have been characterized in the mouse stomach (Tsuchiya et al, 2009). We propose a metabolic pathway (Fig.…”
Section: Farrell Et Almentioning
confidence: 99%